Trends in mortality from alcohol, opioid, and combined alcohol and opioid poisonings by sex, educational attainment, and race and ethnicity for the United States 2000-2019 - Buckley, Charlotte; Ye, Yu; Kerr, William C.; Mulia, Nina; Puka, Klajdi; Rehm, Jürgen; Probst, Charlotte (BMC medicine, 2022)
The ongoing opioid epidemic and increases in alcohol-related mortality are key public health concerns in the USA, with well-documented inequalities in the degree to which groups with low and high education are affected. This study aimed to quantify disparities over time between educational and racial and ethnic groups in sex-specific mortality rates for opioid, alcohol, and combined alcohol and opioid poisonings in the USA.